PEMAMFAATAN CANGKANG SAWIT SEBAGAI AGREGAT KASAR PADA CAMPURAN ASPHALT CONCRETE BINDER COARSE (AC-BC) DENGAN METODE PERCENTAGE REFUSAL DENSITY (PRD). - Lusyana, Lusyana; Mukhlis, Mukhlis; Ali, Syaifullah; Adibroto, Fauna; Duharmen, Zikri (Jurnal Ilmiah Rekayasa Sipil, 2019)
The road in west sumatera generally using flexible pavement, asphalt concrete binder course is used to hold the travic load, that’s why it is necessary to have a mixture with enough strength (Ariawan, 2007). Palm is one of nature resource which is widely available in west sumatera that produce palm oil. Pecentage refusal density is a state where asphalt mix that being compacted is much more bigger as simulation for secondary density, so when the mixture can’t be compacted anymore because of VIM refusal is decreasing result from the compacting until the ultimate state. The purpose of this research is to get the optimum bitumen content refusal with percentage refusal density method start from VIM refusal limit state ≤ 2% from the mixture with palm oil percentage 0%; 2,5%; 5%; 7,5%; 10%; 12,5%; and 15%, as the coarse aggregate substitute. The result from research show that the value of optimum bitumen content refusal from each mixture is 5,5%; 5,55%; 6,05%; 6,1%; 6,35%; 6,35%; and 6,45%. From research result, the sample of asphalt concrete binder course mixture with palm oil as substitute is satisfy the standard and can be used.